Innovative use of sheep and goats by women in climate smart villages in Kenya - Ojango, Julie M.K.; Audho, James O.; Oyieng, Edwin P.; Recha, John W.M.; Muigai, Anne W.T. (2018)
The Nyando Basin in Kenya, a rich agricultural flood plain around Lake Victoria with a population density exceeding 400 persons per square kilometre, has been adversely affected by extreme weather events that include droughts and floods. Literacy levels are low. Land sizes are small, generally less than one hectare, and poverty rates are high. Through a partnership around collective action, seven villages have been selected to pilot climate smart integrated crop and livestock production. The approach focusses on improving local knowledge of climate risks, variability in seasonal rainfall, and targeted introduction of technologies to increase productivity of crops and livestock in order to enhance livelihoods. Given the household composition and differential access and control over resources by men and women in the communities a gendered approach was adapted for sheep and goat improvement. Men generally control practices around goats, while women have a greater say on sheep. Past uncontrolled breeding of sheep and goats, closed to introduction of animals from elsewhere has resulted in smaller sized animals that take long to mature, and do not fetch good market prices. The CGIAR led project thus introduced improved strains of resilient but more productive indigenous breeds of Gala goats and Red Maasai sheep for crossbreeding with the local breeds and has resulted in women taking a lead in community led breeding programmes resulting in crosses with better performance and desirable traits.